Pathways of grazing effects on soil organic carbon and nitrogen - Piñeiro, Gervasio (2010)
Grazing modifies the structure and function of ecosystems, affecting soil organic carbon (SOC) storage. Although grazing effects on some ecosystem attributes have been thoroughly reviewed, current literature on grazing effects on SOC needs to be synthesized. Our objective was to synthesize the effects of grazing on SOC stocks in grasslands, establishing the major mechanistic pathways involved. Additionally, and because of its importance for carbon (C) biogeochemistry, we discuss the controls of soil organic nitrogen (N) stocks. We reviewed articles analyzing grazing effects on soil organic matter (SOM) stocks by comparing grazed vs. ungrazed sites, including 67 paired comparisons. SOC increased, decreased, or remained unchanged under contrasting grazing conditions across temperature and precipitation gradients, which suggests that grazing influences the factors that control SOC accumulation in a complex way. However, our review also revealed some general patterns such as 1) root contents (a primary control of SOC formation) were higher in grazed than in their ungrazed counterparts at the driest and wettest sites, but were lower at sites with intermediate precipitation (~400 mm to 850 mm); 2) SOM C:N ratios frequently increased under grazing conditions, which suggests potential N limitations for SOM formation under grazing; and 3) bulk density either increased or did not change in grazed sites. Nearly all sites located in the intermediate precipitation range showed decreases or no changes in SOC. We grouped previously proposed mechanisms of grazing control over SOC into three major pathways that can operate simultaneously: 1) changes in net primary production (NPP pathway), 2) changes in nitrogen stocks (nitrogen pathway), and 3) changes in organic matter decomposition (decomposition pathway). The relative importance of the three pathways may generate variable responses of SOC to grazing. Our conceptual model suggests that rangeland productivity and soil carbon sequestration can be simultaneously increased by management practices aimed at increasing N retention at the landscape level.